The Effect of Managerial Ownership, Institutional Ownership, Dividend Payout Ratio, and Debt to Equity Ratio on Stock Price - Widiono, Ribut; Yuniarwati (LifeSciFi, 2025)
Stock price movements represent market responses to corporate governance and financial policy decisions. This study analyzes the factors influencing stock prices in manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The variables examined include managerial ownership, institutional ownership, dividend payout ratio, and debt-to-equity ratio. This research adopts a quantitative approach using secondary data obtained from audited annual reports and financial statements. The sample was determined through purposive sampling, consisting of manufacturing firms that operated consecutively for three years, reported financial statements in IDR, distributed dividends, and did not experience consecutive losses. Using these criteria, 20 companies were selected, resulting in 60 firm-year observations. Data were analyzed using Partial Least Squares Structural Equation Modeling to examine the direct effects of the independent variables on stock prices. The results indicate that managerial ownership, institutional ownership, DPR, and DER significantly influence stock prices. Organizational and institutional ownership enhance investor confidence, dividend policy serves as a positive signal of firm performance, and capital structure affects investors’ perceptions of risk. These findings provide implications for investors and corporate management in investment decision-making. However, this study is limited to a specific sample and period and does not include mediating or moderating variables.